Порівняння підходів до створення програм для мобільних пристроїв - Скворцов, В. Х. (ХНУРЕ, 2024)
This work is dedicated to comparing two main approaches to mobile application development: native apps, specifically adapted to certain operating systems, and web applications, accessed through a web browser. The characteristics of each approach, their advantages, and disadvantages are discussed. It is noted that native apps provide high performance and tight integration with the operating system, while web applications offer greater accessibility and scalability. The conclusions of the work enable a better understanding of which development approach to choose depending on the specific needs of the project and the conditions of application use.
Keywords: мобільний пристрій